CH3NH3PbBr3 nanocubes-array for solar cell application. (February 2018) - Swain, Bhabani Sankar; Sheikh, Md. Abdul Kuddus; Singh, Son; Abdur, Rahim; Jeong, Daekyun; Lee, Jaegab
Abstract: Methyl-ammonium lead bromide (MAPbBr3 ) is currently studying due to its potential application to high open circuit voltage photovoltaic device. Due to the limited solubility of methyl ammonium bromide (MABr) in iso-propyl alcohol (IPA), the MAPbBr3 was only fabricated by one step (1-step) spin coating process. In this article, we alternatively used ethanol and methanol as solvent to dissolve MABr to fabricate MAPbBr3 films by two steps (2-steps) spin coating process. As a result, we observed a dense, closed stacked and aligned perovskite nanocubes array using a varying concentration of MABr and waiting time. Our best device with an architecture of FTO/TiO2 /MAPbBr3 /Spiro-OMeTAD/Au shows a current density of 9.31 mA/cm 2, open circuit voltage of 1.05 V, and fill factor of 0.58 with a power conversion efficiency of 5.70%. We were optimistic that these MAPbBr3 nanocube arrays would be applicable to solar cell as well as other optoelectronic devices such as photodetector, light emitting diode and X-ray scintillator. Graphical abstract: